2011
DOI: 10.1016/j.fertnstert.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial support for infertile couples during assisted reproductive technology treatment

Abstract: Men might feel excluded from the treatment because of the greater attention to women, leading to feelings of isolation from friends and partners. Women suffer particularly in cases of failure that reconfirms the trauma of infertility. These psychological risk factors underline the usefulness of psychological support for these couples, especially in cases of prolonged infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
(18 reference statements)
2
23
0
Order By: Relevance
“…A Swedish study 28 found that for men, common sources of support included friends (38%) and their own mothers (27%) and fathers (23%), but a large proportion (47.3%) had not confided in anyone other than their spouse. In Italy, Agostini et al 73 conducted a cohort study of 83/161 (51%) couples from treatment initiation to 1 month after embryo transfer and investigated perceived social support using the Multidimensional Scale of Perceived Social Support. 74 At all time points studied, men were found to have less social support and to be less likely to discuss infertility and treatment with others than women.…”
Section: Male Experiences Of Infertility Treatmentmentioning
confidence: 99%
“…A Swedish study 28 found that for men, common sources of support included friends (38%) and their own mothers (27%) and fathers (23%), but a large proportion (47.3%) had not confided in anyone other than their spouse. In Italy, Agostini et al 73 conducted a cohort study of 83/161 (51%) couples from treatment initiation to 1 month after embryo transfer and investigated perceived social support using the Multidimensional Scale of Perceived Social Support. 74 At all time points studied, men were found to have less social support and to be less likely to discuss infertility and treatment with others than women.…”
Section: Male Experiences Of Infertility Treatmentmentioning
confidence: 99%
“…Infertility diagnosis and the treatment failures are sudden, unexpected, and frightening crisis that can affect the adaptation process of couples. In addition, mental pressure, loneliness, disappointment, and loss of control are highly observed in people referring for assisted reproductive methods (11,12). Studies have shown that such factors as age at the time of infertility diagnosis, infertility duration, marriage duration, cause of infertility, treatment failure, frequent pregnancy tests, and more importantly social stigma lead to the creation of infertilityrelated stress in couples (7,11,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The negative consequences found in many studies and reviews included increased levels of stress, confusion and anxiety [5] [6] [7], decreased satisfaction with the couples' relationship and sexuality [8] [9], decreased satisfaction with social life and, in unsuccessful treatments, hampered grieving [10] [11] and lasting sadness [12]. These negative consequences are found in both men and women, and while some authors suggest these consequences may be somewhat stronger in women [8] [13] [14], others did not [12] [15].…”
Section: Introductionmentioning
confidence: 99%